SIZE AND COMPOSITION DEPENDENT MICROSTRUCTURE AND MAGNETIC PROPERTIES OF ZnCo Cr O (x=0 to 0.8) - G., Jagadish Kumar (IIT (BHU) varanasi, 2018)
Spinel compounds, AB2O4 (where, A and B are the divalent and trivalent cations) are attractive for their wide range of applications such as catalysts and sensors (Yamasaki et al., 2006 and Tomiyasu et al., 2004). While in normal spinel, the divalent cations (Mg, Mn, Ni, Zn, Co) occupy the tetrahedral (A) site and trivalent cations (Al, Cr, Fe) prefer the octahedral (B) sites, in an inverse spinel, the divalent cations prefer one of the B site and the trivalent cations are equally distributed among A and B sites. In mixed spinels, two or more different kinds of divalent cations are distributed between A and B sites. Thus, the magnetic behavior in these compounds is sensitive to the type of cations and their distribution among A and B sites of the lattice. The magnetism in spinels mainly originates from the exchange interaction of unpaired electrons between cations occupying the A and B sites. As a result, properties can be modulated and materials can be tuned for technological applications. The MCr2O4 (M = Mn, Co, Ni, Zn, Mg, Fe) are ferrimagnetic spinels, in which the M+2 cations occupy the tetrahedral sites and Cr3+ cations occupy the octahedral sites. One of the spinel of general formula MCr2X4 (M= Mn, Fe; X=O, S) exhibits many unusual magnetic properties such as ferrimagnetism, colossal magnetoresistance, magnetoelectric coupling etc. Chromites with spinel structure are focused in solid-state sciences due to their broad range of functions (Melot et al., 2009). One of the chromite i.e., cobalt chromite has attracted much attention because of its multiferroic behavior as well as fascinating temperature and magnetic field dependent magnetoelectric properties (Yamasaki et al. 2006). The uniqueness of CoCr2O4 is as it not only displays uniform polarization and spatially modulated magnetism but also exhibits uniform magnetization in the conical cycloid state. CoCr2O4 exhibits a rich sequence of magnetic transitions such as paramagnetic to collinear ferrimagnetic ordering at Curie temperature, TC (94 K) and non-collinear spiral ordering at TS, 23K and finally to a lock-in transition, TL, 15 K (Tomiyasu et al., 2004 ). Yamasaki et al., Phys. Rev. Lett. 96 (2006) 207204; Tomiyasu et al., Phys. Rev. B 70 (21) (2004) 214434; Tomiyasu et al., Physica B 392 (2007) 16-19; Melot et al., Journal of Physics: Condensed Matter 21 (2009) 216007; Lawes et al., Phys. Rev. B 74 (2006) 024413. 3 With decreasing temperature from 300 K, the consequence of high crystal field stabilization energy of Cr3+ (2.02 eV) which leads to strong anti-ferromagnetic B-B interaction over A-B (Dwight et al., 1969). As a result, the anti-ferromagnetic alignment between A and B sites is completely destroyed and system exhibits a screw ordering. This is otherwise named as ferrimagnetic spiral wherein the spins lie on the conical surfaces. Some reports found on magnetic transitions focused on bulk and single crystals of CoCr2O4. Menuk et al. have shown in bulk sample, that below TC, magnetic ordering consists of a ferrimagnetic component and a spiral component through neutron diffraction and magnetic measurements (Menuk et al., 1964). The ferrimagnetic component exhibits long range order at all temperatures below TC while the spiral component exhibits a short range order. Lawes et al. further reports a dielectric anomaly below spiral magnetic order (Lawes et al.,2006). The spiral component induces electric polarization and also a spontaneous magnetization for which it is said to be as multiferroic. Tomiyasu et al. revisit the spiral ordering by neutron scattering and magnetic measurements in CoCr2O4 single crystals and have shown a simultaneous formation of long range ferrimagnetic component and a short range spiral component at lowest temperature phase (Tomiyasu et al., 2004). Severance et al. have shown that with increase in temperature from 10 to 45K, intensity of the magnetic satellite peak decreases (Severance et al., 1993). At 50 K, the intensity of the diffuse peak diminishes to the background level, indicating that short-range magnetic order is completely vanished. Incommensurate to commensurate transition of the propagation vector is observed at spiral ordering temperature by Plumier et al and Yamasaki et al. investigate that the compound undergoes a transition to a conical spin structure with an incommensurate propagation vector at TS = 26 K, and a lock-in transition at around 15K (Plumier et al., 1968). Moreover, scarce reports on CoCr2O4 generates a lot of dispute on magnetic transitions i.e. whether short range or long range, spiral ordering is whether commensurate or incommensurate etc . Menyuk et al., Le Journal De Physique, 25 (1964) 528; Severance, et al., Am. Miner. 78 (1993) 724-732; Plumier et al., Journal of Applied Physics 39 (2) (1968) 635-636; Dwight et al., Journal of Applied Physics 40 (3) (1969) 1156-1157; Barrera et al., J. Magn. Mang. Mater. 456 (2018)372-380
Keywords: MICROSTRUCTURE ,MAGNETIC PROPERTIES , ZnCo Cr O (x=0 to 0.8)